PROTOKOL JOHOR - Abdul Rahim Ramli, 1941-, author 258518; Kassim Thukiman, 1963-, editor 557528; Ahmad Fadhli Syed Hassan, 1987-, editor 621259 (Johor Bahru, Johor : PENERBIT UTM PRESS, 2024)
Includes bibliographical references and index.